Qualitative methods in workplace learning - Fabritius, Hannele (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
Methods of learning in the workplace will be introduced. The methods are connect to competence development and to the process of conducting development discussions in a dialogical way. The tools developed and applied are a fourfold table, a cycle of work identity, a plan of personal development targets, a learning meeting and a learning map. The methods introduced will aim to better learning at work.